Contraceptive Use and Its Associated Factors among Women Who Gave Birth within 12 Months in Dubti Town, Pastoral Community, of Afar Region Northeast, Ethiopia - Abdu Yimam; Girmatsion Fisseha; Mebrahtu Kalayu; Etsay Woldu Anbesu (Hindawi Limited, 2021)
Introduction. Substantial numbers of women are not using contraceptives in their postpartum period and die due to avoidable causes related to birth complications. Contraceptives use within 12 months of childbirth has given less attention in Ethiopia. Thus, this study is aimed to assess contraceptive use and its associated factors among women who gave birth within 12 months in Dubti town, pastoral community of Afar region, Ethiopia. Methods. A community-based cross-sectional study was conducted among 342 women in the Dubti town. A systematic random sampling technique was employed to identify and enroll women. Data were collected using a pretested, structured, and interviewer-administered questionnaire. Descriptive statistics were done, and logistic regression analysis was employed to identify the factors associated with contraceptive use. The statistical association was measured by odds ratio with a 95% confidence interval. p value < 0.05 was considered as statistically significant. Results. In this study, 103 (30.1%) [95% CI: 25.4%, 35.1%] women have used contraceptives. Women who had secondary educational level (AOR=3.53, 95% CI (1.68, 7.36), had antenatal care follow-up (AOR=1.93, 95% CI (1.01, 3.69), and visited by health worker after delivery (AOR=2.54, 95% CI (1.37, 4.68) were associated with increased odds of contraceptives use. Conclusions. This study revealed that the prevalence of contraceptive use was low compared to the national recommended figure. Secondary educational level, having antenatal care follow-up, and being visited by health workers after delivery were predictors of contraceptive use. Thus, increase the educational status of women, antenatal care follow-up service, and visiting after delivery by health workers are important interventions to promote the use of contraceptives in the postpartum period.